THE USE OF DIGITAL DENTAL CALCULATOR APPS AS AN PHPM CALCULATION TOOL: A QUASI-EXPERIMENTAL - Nada, Utari Meria; Yandi, Satria; Ningrum, Valendriyani (FKG ULM, 2026)
Background: The Personal Hygiene Performance Modified (PHP-M) index is a widely used tool for assessing oral hygiene status, but manual calculations are time-consuming and susceptible to human error. Digital dental calculator apps may streamline this process, yet their efficacy in PHP-M scoring remains underexplored. Objective: This study evaluated the duration time of a digital dental calculator app for PHP-M calculations compared to traditional manual methods. Methods: A quasi-experimental study was conducted with 65 dental professional students. Convenience sampling technique was employed, and the selected samples satisfied the established inclusion and exclusion criteria. The inclusion criteria were students of the dental profession at Baiturrahmah University in Indonesia who were still enrolled or had passed the pedodontics module. Conversely, students who did not participate in the full study (manual and digital) were excluded from the study. Participants assessed PHP-M score used standard scenario. First, participants was conducted traditional manual methods and the two weeks later used digital calculator for calculate the PHP-M scores. Results: The mean time taken to calculate PHP-M results manually was 136.75 seconds, while the mean time taken to calculate the same results using the digital dental calculator application was 48.49 seconds. The results of the Mann-Whitney test demonstrate that there is a statistically significant discrepancy between manual and digital calculations utilizing the application, with a p-value of 0.000 (p <0.05).Conclusion:Digital dental calculator apps significantly enhance the speed, and usability of PHP-M index calculations. Their adoption in clinical and research settings can improve oral hygiene assessments and standardize reporting.Keywords: Dental calculator app, Digital dentistry, Duration time, PHP-M index